Foreign tourist behavior and perception of motorcycle accident risk in Chiang Mai, Thailand - P. Iamtrakul; S. Chaypong; J. Klaylee (Lowland Technology International, 2019)
Motorcyclists are one of the most vulnerable road user groups in developing world, especially Thailand. Due to its propensity to threats during traveling, tourism industry has some reservations on its quality and adequacy for travel. More specifically, traveling with motorcycles in unfamiliar route has been found to be a major risk for all motorcyclists. Thus, this study aimed to explore relationship this risk poses to the foreign tourists with respect to socio-economic, knowledge and perceptions of those motorcyclists, by conducting the site investigation together with a questionnaire survey. A total of 400 samplings of foreign tourists in Chiang Mai, Thailand was analyzed by applying logistic regression based on binary model. This research found the important factors influencing this risk behavior relatively in high proportional order as follows; 1) understanding of the traffic regulations and 2) possession of adequate and valid travel insurance. Therefore, safety knowledge training especially as it relates to traffic regulation for accident prevention could play a key role in prevention of motorcycle‐related injuries and fatalities. This promising intervention in highly recommended in environments where road safety measures, particularly enforcement activities, are commonly limited.